Valuasi Ekonomi pada Wisata Pantai Pondok Permai dengan Travel Cost Model Perspektif Ekonomi Islam - Maulida Marpaung; Isnaini Harahap; Wahyu Syarvina (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This Research used a quantitative descriptive method, using primary data in determining the sample, namely purposive random sampling using the slovin formula. This research aims to determine the effect of the independent variant (distance, travel cost,facilities) on the dependen variable (number of visits) to pondok Indah beach tourism. This research used the travel cost model (TCM) approach to determine the factors that influence the number of visits and estimate the economic value of Pondok permai beach. The result showed that the travel cost and facilities variable had a significant effect and the distance variable had no significant effect. From the calculation result, it is known that the economic value of Pondok permai beach tourism is Rp. 5.573.750.000 per year with a consumer surplus value of Rp.796.250 per individual per visit within a one year period. Based on Islamic perspective, Pondok permai beach tourism has implemented several criteria for halal tourism, such as protecting the coastal environment, managing and developing it wisely, providing prayer facilities and providing food and drinks that are guaranteed to be halal. Keywords: Economic Valuation, Travel cost model, beach tourism, Islamic economic perspective.